Step by step : tubo uterine factors in infertility - Ghumman, Surveen; Singh Kumar, Neena; Bhardwaj, Punita; Sahni, Reeti; Salhan, Sudha; Ghumman, Surveen; Mittal, Shweta (Nueva Delhi : Jaypee, 2007)
The book attempts to roadmap the latest therapies, defining their current relevance to diagnosis and treatment, in a simplified, easy to follow protocol for the practicing infertility specialist with flow charts for management providing guidance in a step by step manner. At the same time besides giving practical guidance, it also touches on the latest research work done in the field. A comprehensive classification, investigation and management of all tubo-uterine factors causing infertility have been presented in the book and the accompanying DVD-ROM. The DVD-ROM shows among others, the technique of endoscopic management of endometrioma, ectopic pregnancy, myoma, intrauterine adhesions, tubal and peritubal pathologies. This book has been written with the aim of placing the modern approach to the management of infertility in the context of sound theory. evidence based therapy and recent advances. In this day of information overload this book is and attempt to integrate information into a practice management protocol that is rational, logical and rewarding for the reader.
1. Evaluation of Uterine Cavity and Endometrium Surveen Ghumman 2. Tests for Evaluation of Tubal Structure and Function Surveen Ghumman 3. Fibroid Surveen Ghumman 4. Endoscopic Management of Fibroid Neena Singh Kumar, Surveen Ghumman 5. Uterine Anomalies Surveen Ghumman 6. Intrauterine Adhesions Surveen Ghumman 7. Hysteroscopic Infertility Surgery Punita Bhardwaj 8. Tubal Reconstructive Surgery Surveen Ghumman 9. Laparoscopic Surgery for Tubal and Peritubal Pathology in Infertility Punita Bhardwaj 10. Laparoscopic Tubal Anastomosis Neena Singh Kumar, Surveen Ghumman 11. Pelvic Inflammatory Disease Surveen Ghumman 12. 12. Endometriosis Surveen Ghumman 13. Ovarian Endometriosis-Laparoscopic Management Neena Singh Kumar, Surveen Ghumman 14. Ectopic Pregnancy Sudha Salhan, Surveen Ghumman 15. Prevention of Postoperative Adhesions Surveen Ghumman 16. 16. IVF and Tubo-uterine Factors in Infertility Shweta Mittal 17. Imaging Techniques in Tubo-uterine Pathology Reeti Sahni Index
Incluye índice
Incluye ilustraciones
Incluye bibliografía
Keywords: INFERTILITY; UTERINE CAVITY; LAPARASCOPIC TUBAL; TUBO UTERINO; INFERTILIDAD